Standardization Of The Recipe For Randang Daging And Additional Ingredients In Padang Panjang City - Feby Mellisa Pratiwi; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This study aims to standardize the recipe for randang daging and additional ingredients to utilize local ingredients as identity in Padang Panjang city which includes ingredients, spices, tools, processing methods, diferences in the use of additional ingredients, cooking techniques and the dosage in randang processing so that various qualities are produced. This type of researsh is a combination of qualitative and quantitative research. Qualitative data sources were obtained from 16 informants who were experts in making randang and quantitative sources were obtained from 10 trained panelist who knew about randang and 5 limited panelist, namely lecturers of family welfare science, FPP, Padang State University. Qualitative data collection techniques are observation, interviews, documentation and quantitative data collection techniques are organoleptic test formats. The organoleptic test of the standart recipe for randang daging resulted in a fairly square shape, the form of cassava was produced quite square, the meat was quite blackish brown, the breast was quite blackish brown, the aroma was quite fragrant, the meat was quite tender, the dadak randang was textured quite dry, oily, sweet potato,the texture of cassav is quite fragile, the taste of the meat is delicious and the taste of cassava is quite absorbent.